Perfluoroalkyl substances and thyroid function in older adults. (February 2015) - Shrestha, Srishti; Bloom, Michael S.; Yucel, Recai; Seegal, Richard F.; Wu, Qian; Kannan, Kurunthachalam; Rej, Robert; Fitzgerald, Edward F.
Abstract: Current understanding of the thyroid disruptive properties of perfluoroalkyl substances (PFASs), particularly in aging populations, is limited. The objectives of this study were to (i) assess associations between thyroid function, as measured by serum thyrotropin (thyroid stimulating hormone, TSH), free thyroxine (fT4), total thyroxine (T4), and total triiodothyronine (T3), and serum perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) in an aging population and (ii) determine if other persistent organic pollutants with thyroid disruptive properties including polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) modify such associations. We conducted a cross-sectional study of 87 men and women 55 to 74 years of age, without clinically-diagnosed thyroid disease, who resided in upper Hudson River communities in New York. Geometric means (standard deviations) of serum PFOS and PFOA were 31.6 (1.7) ng/mL and 9.17 (1.72) ng/mL, respectively. Multivariable linear regression analyses indicated that one interquartile range difference in PFOS corresponded to 4% and 9% increases in fT4 and T4 respectively. We detected statistical interactions between PFOA and age for effects on fT4 and T4; joint increases in PFOA and age were associated with increases in fT4 and T4, of 3% and 7%, respectively. We also detected statistical interactions between PFOS and total PCBs for the effect on T3 and between PFOA and total PBDEs for the effect on TSH. Our results suggest that PFASs are associated with subtle alterations in thyroid hormone levels in this population, and that these associations are likely to vary by age, and levels of PCBs and PBDEs. Highlights: Associations between PFASs and thyroid hormones were assessed in older adults. Free and total thyroxine were positively associated with serum PFOS. Age, PCBs, and PBDEs may modify the associations of PFASs with thyroid hormones.